Photoresist bottom anti-reflective coating polymer, preparation method, composition and application
By applying a new type of anti -reflex coating polymer at the bottom of the light -engraved glue, the problem of poor anti -reflex coating performance in existing technologies has been solved, the effect of high resolution and low reflectivity is achieved, and the process is improved. Stability and efficiency.
Patent Information
- Application Number
- CN202411649151.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Existing photoresist bottom anti-reflective coatings do not perform well in high resolution and low reflectivity, and the preparation process is complex and expensive, difficult to remove and prone to pattern floating.
Provide a kind of anti -reflex coating polymer at the bottom of the lithographic glue. By reflecting the single A, single B, single C, and catalyst in the electronic -grade solvent in an inert gas atmosphere to control the reaction temperature and time, it is preparation for high high. Anti -reflex coating of discount rate n and eliminating coefficient K.
The polymer forms a high -quality anti -reflex coating through synergy, significantly improved the resolution of the photocopy glue pattern, and has high stability and excellent etching rate, avoiding the pattern floating.
Smart Images

Figure CN119165732B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a photoresist bottom anti-reflection coating polymer, a preparation method, a composition and an application thereof, and belongs to the technical field of photoresists. Background Art
[0002] The bottom anti-reflective coating (BARC) of photoresist refers to a thin film coating applied between the photoresist and the substrate that can effectively eliminate the degradation of imaging quality caused by light reflection on the substrate surface. With the development of science and technology, the photolithography process has shown a trend of miniaturization, and the wavelength of exposure light has become shorter. The reflection of the bottom semiconductor wafer will be stronger, and the negative impact of reflected light on the line width resolution of the photoresist will be more significant. Therefore, the performance requirements for anti-reflective coatings are getting higher and higher.
[0003] According to the materials used, the bottom anti-reflection coating can be divided into inorganic bottom anti-reflection coating and organic bottom anti-reflection coating. Known inorganic bottom anti-reflection coatings are made of titanium, titanium dioxide, titanium nitride, chromium oxide, carbon, amorphous silicon, etc. The preparation process is complicated, the required equipment is relatively expensive (such as vacuum evaporator, chemical vapor deposition (CVD) equipment, sputtering equipment, etc.), and it is not easy to remove in the subsequent process, and the pattern often floats. The organic bottom anti-reflection coating mainly refers to a polymer compound material containing a light-absorbing substance. The preparation process does not require complex equipment and can be cured at high temperature. However, the organic bottom anti-reflection coating still needs to meet the requirements of having a large absorbance to the reflected light, being insoluble in the photoresist, having no diffusion of low molecular weight substances during coating and curing, and having a relatively excellent etching rate in the dry etching process of the photoresist.
[0004] Therefore, it is very important to invent a bottom organic anti-reflection coating with high anti-reflection effect and excellent etching rate, and to improve the refractive index n and extinction coefficient k of the anti-reflection coating formed by baking and curing the existing bottom anti-reflection coating composition. Summary of the invention
[0005] The present invention aims at the deficiencies in the prior art and provides a photoresist bottom anti-reflective coating polymer, a preparation method, a composition and an application. The bottom coating prepared by using the bottom anti-reflective coating polymer has a high refractive index n and an extinction coefficient k, can effectively prevent light from penetrating the anti-reflective coating after reflection, reduce the standing wave effect, and significantly improve the resolution of the photoresist development pattern.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a photoresist bottom anti-reflective coating polymer, the polymer has the following general formula:
[0007] ;
[0008] a, b, and c are respectively the mass fractions of the polymer repeating units; a is selected from 15-55%, b is selected from 20-70%, and c is selected from 10-40%; the weight average molecular weight of the polymer is selected from 1000-10000 Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.0-3.0.
[0009] Preferably, a is selected from 25-40%, b is selected from 40-60%, and c is selected from 15-30%.
[0010] Preferably, the weight average molecular weight of the polymer is selected from 4000-8000 Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.4-2.3.
[0011] The present invention also discloses a method for preparing a photoresist bottom anti-reflective coating polymer, the preparation method comprising: reacting monomer a, monomer b, monomer c and a catalyst in an electronic grade solvent under an inert gas atmosphere, controlling the reaction temperature and reaction time, and obtaining the polymer through post-treatment after the reaction is completed;
[0012] The monomer a is diglycidyl terephthalate, the monomer b is 5-ethyl-5-(p-tolyl)malonyl urea, and the monomer c is triglycidyl isocyanurate.
[0013] Further, the catalyst is any one of benzyltriethylammonium chloride, tetrabutylammonium chloride, and tetraethylammonium bromide;
[0014] The electronic grade solvent is any one of propylene glycol methyl ether (PGME), 2-hydroxyisobutyric acid methyl ester (HBM), propylene glycol methyl ether acetate (PGMEA), 3-methoxypropionic acid methyl ester (MMP), ethyl lactate, cyclopentanone, and dipropylene glycol methyl ether.
[0015] Furthermore, the amount of the catalyst used is 1-10% of the total mass of the monomer a, monomer b, and monomer c;
[0016] The reaction temperature is 60-150° C., and the reaction time is 8-15 hours.
[0017] The invention also discloses a photoresist bottom anti-reflection coating composition, wherein the photoresist bottom anti-reflection coating comprises the polymer of the invention, a cross-linking agent, a photoacid generator and an electronic grade solvent.
[0018] Furthermore, the mass fraction of the polymer in the composition is 2-10%, the mass fraction of the crosslinker in the composition is 1-3%, the mass fraction of the photoacid generator in the composition is 0.01-0.05%, and the mass fraction of the electronic grade solvent in the composition is 90-95%.
[0019] Further, the cross-linking agent is at least one of hexamethoxymethyl melamine, hexabutoxymethyl melamine, tetramethoxymethyl glycoluril, 1,3,4,6-tetrakis (butoxymethyl) glycoluril, tetramethoxymethyl benzoguanamine, and N-hydroxymethyl acrylamide;
[0020] The photoacid generator is any one or a combination of 1-((3-hydroxyadamantyl)methoxycarbonyl)-difluoromethanesulfonic acid triphenyl sulfide, p-toluenesulfonic acid triphenyl sulfide, trifluoromethanesulfonic acid (p-tert-butoxyphenyl) diphenyl sulfide, 4-tert-butylphenyl diphenyl sulfide nonafluorobutane sulfonate, bis(benzenesulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, trifluoromethanesulfonic acid tri(p-tert-butoxyphenyl) sulfide;
[0021] The electronic grade solvent is any one of methyl 2-hydroxyisobutyrate, propylene glycol methyl ether, methyl isobutyl carbinol, propylene glycol monomethyl ether acetate, and dipropylene glycol methyl ether.
[0022] The invention also discloses an application of a photoresist bottom anti-reflection coating composition, wherein the composition is applied to an ArF photoresist bottom anti-reflection coating.
[0023] The beneficial effects of the present invention are:
[0024] (1) The polymer involved in the present invention forms a bottom anti-reflective coating with good coating quality through the synergistic effect of various components through cross-linking and curing, has excellent high differential solubility, and does not mix with the top photoresist material.
[0025] (2) The photoresist bottom anti-reflective coating composition provided by the present invention has extremely high stability. After long-term storage and then drying and curing, the refractive index n and extinction coefficient k of the bottom anti-reflective coating obtained remain basically unchanged, and the excellent performance is still maintained, which provides sufficient convenience for the industrialization process.
[0026] (3) The bottom anti-reflective coating of the photoresist provided by the present invention is applied before the photoresist to obtain a BARC layer that has strong absorption to the photolithography wavelength, so that the reflected light from the interface between the photoresist and the BARC layer and the interface between the BARC layer and the substrate undergoes destructive interference, thereby reducing the total reflected light intensity.
[0027] (4) The anti-reflection coating layer at the bottom of the photoresist provided by the present invention has a high refractive index n and extinction coefficient k, which allows the use of a thinner anti-reflection layer, thereby shortening the etching time and providing a higher etching rate, thereby preventing excessive loss of the photoresist film during the etching process due to the low etching rate. At the same time, the anti-reflection layer with a shorter etching time can be applied to thin-layer photoresists, thereby obtaining high-resolution photolithography patterns. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The polymer obtained in Synthesis Example 1 1 H-NMR spectrum. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0031] A photoresist bottom anti-reflective coating polymer, the polymer having the following general formula:
[0032] ;
[0033] a, b, and c are respectively the mass fractions of the polymer repeating units; a is selected from 15-55%, b is selected from 20-70%, and c is selected from 10-40%; the weight average molecular weight of the polymer is selected from 1000-10000 Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.0-3.0.
[0034] Preferably, a is selected from 25-40%, b is selected from 40-60%, and c is selected from 15-30%.
[0035] Preferably, the weight average molecular weight of the polymer is selected from 4000-8000 Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.4-2.3.
[0036] A method for preparing a photoresist bottom anti-reflective coating polymer, the preparation method comprising: reacting monomer a, monomer b, monomer c and a catalyst in an electronic grade solvent under an inert gas atmosphere, controlling the reaction temperature and reaction time, and obtaining the polymer through post-treatment after the reaction is completed;
[0037] The monomer a is diglycidyl terephthalate, the monomer b is 5-ethyl-5-(p-tolyl)malonyl urea, and the monomer c is triglycidyl isocyanurate.
[0038] Further, the catalyst is any one of benzyltriethylammonium chloride, tetrabutylammonium chloride, and tetraethylammonium bromide;
[0039] The electronic grade solvent is any one of propylene glycol methyl ether (PGME), 2-hydroxyisobutyric acid methyl ester (HBM), propylene glycol methyl ether acetate (PGMEA), 3-methoxypropionic acid methyl ester (MMP), ethyl lactate, cyclopentanone, and dipropylene glycol methyl ether.
[0040] Preferably, the catalyst is benzyltriethylammonium chloride; and the electronic grade solvent is propylene glycol methyl ether (PGME).
[0041] Furthermore, the amount of the catalyst used is 1-10% of the total mass of the monomer a, monomer b, and monomer c;
[0042] The reaction temperature is 60-150° C., and the reaction time is 8-15 hours.
[0043] Preferably, the amount of the catalyst is 2-5% of the total mass of the monomer a, monomer b, and monomer c;
[0044] The reaction temperature is 100-120° C., and the reaction time is 10-12 hours.
[0045] The invention also discloses a photoresist bottom anti-reflection coating composition, wherein the photoresist bottom anti-reflection coating comprises the polymer of the invention, a cross-linking agent, a photoacid generator and an electronic grade solvent.
[0046] Furthermore, the mass fraction of the polymer in the composition is 2-10%, the mass fraction of the crosslinker in the composition is 1-3%, the mass fraction of the photoacid generator in the composition is 0.01-0.05%, and the mass fraction of the electronic grade solvent in the composition is 90-95%.
[0047] Preferably, the mass fraction of the polymer in the composition is 4-6%, the mass fraction of the crosslinker in the composition is 2%, the mass fraction of the photoacid generator in the composition is 0.05%, and the mass fraction of the electronic grade solvent in the composition is 91.5-94.0%.
[0048] Further, the cross-linking agent is at least one of hexamethoxymethyl melamine, hexabutoxymethyl melamine, tetramethoxymethyl glycoluril, 1,3,4,6-tetrakis (butoxymethyl) glycoluril, tetramethoxymethyl benzoguanamine, and N-hydroxymethyl acrylamide;
[0049] The photoacid generator is any one or a combination of 1-((3-hydroxyadamantyl)methoxycarbonyl)-difluoromethanesulfonic acid triphenyl sulfide, p-toluenesulfonic acid triphenyl sulfide, trifluoromethanesulfonic acid (p-tert-butoxyphenyl) diphenyl sulfide, 4-tert-butylphenyl diphenyl sulfide nonafluorobutane sulfonate, bis(benzenesulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, trifluoromethanesulfonic acid tri(p-tert-butoxyphenyl) sulfide;
[0050] The electronic grade solvent is any one of methyl 2-hydroxyisobutyrate, propylene glycol methyl ether, methyl isobutyl carbinol, propylene glycol monomethyl ether acetate, and dipropylene glycol methyl ether.
[0051] Preferably, the crosslinking agent is hexamethoxymethyl melamine; the photoacid generator is 1-((3-hydroxyadamantyl)methoxycarbonyl)-difluoromethanesulfonic acid triphenyl sulfide; and the electronic grade solvent is propylene glycol monomethyl ether acetate (PGMEA).
[0052] The invention discloses an application of a photoresist bottom anti-reflection coating composition, wherein the composition is applied to an ArF photoresist bottom anti-reflection coating.
[0053] 1. Polymer synthesis:
[0054] Synthesis example 1
[0055] Under nitrogen protection, 30 g of diglycidyl terephthalate, 50 g of 5-ethyl-5-(p-tolyl)malonyl urea, 20 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of propylene glycol monomethyl ether (PGME), and the temperature was raised to 120°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 67.8 g of a polymer with Mw=6932Da and PDI=1.62. 1 H-NMR (400 MHz, CDCl 3 ), δ=1.338-2.071 (H on ethyl and methyl groups), δ=3.608-4.528 (H on carbon attached to O or N), δ=6.897-8.044 (H on benzene ring), δ=7.651 (H on hydroxyl group). 1 H-NMR Figure 1 shown.
[0056] Synthesis example 2
[0057] Under nitrogen protection, 35 g of diglycidyl terephthalate, 43 g of 5-ethyl-5-(p-tolyl)malonyl urea, 22 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 110°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 63.6 g of a polymer with Mw=6891Da and PDI=1.68.
[0058] Synthesis example 3
[0059] Under nitrogen protection, 30 g of diglycidyl terephthalate, 55 g of 5-ethyl-5-(p-tolyl)malonyl urea, 15 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 120°C. The reaction was kept warm for 10 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 68.4 g of a polymer with Mw=7021Da and PDI=1.66.
[0060] Synthesis example 4
[0061] Under nitrogen protection, 25g of diglycidyl terephthalate, 60g of 5-ethyl-5-(p-tolyl)malonyl urea, 15g of triglycidyl isocyanurate, and 4g of benzyltriethylammonium chloride were dissolved in 300g of PGME, and the temperature was raised to 100°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 61.3g of a polymer with Mw=6754Da and PDI=1.58.
[0062] Synthesis example 5
[0063] Under nitrogen protection, 25 g of diglycidyl terephthalate, 45 g of 5-ethyl-5-(p-tolyl)malonyl urea, 30 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 120°C. The reaction was kept warm for 10 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 59.3 g of a polymer with Mw=6751 Da and PDI=1.59.
[0064] Synthesis example 6
[0065] Under nitrogen protection, 28 g of diglycidyl terephthalate, 42 g of 5-ethyl-5-(p-tolyl)malonyl urea, 30 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 120°C. The reaction was kept warm for 11 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 61.0 g of a polymer with Mw=6834 Da and PDI=1.62.
[0066] Synthesis Example 7
[0067] Under nitrogen protection, 25 g of diglycidyl terephthalate, 55 g of 5-ethyl-5-(p-tolyl)malonyl urea, 25 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 110°C. The reaction was kept warm for 10 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 57.3 g of a polymer with Mw=6921Da and PDI=1.64.
[0068] Synthesis example 8
[0069] Under nitrogen protection, 40g of diglycidyl terephthalate, 45g of 5-ethyl-5-(p-tolyl)malonyl urea, 15g of triglycidyl isocyanurate, and 4g of benzyltriethylammonium chloride were dissolved in 300g of PGME, and the temperature was raised to 120°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 54.5g of a polymer with Mw=6891Da and PDI=1.60.
[0070] Synthesis example 9
[0071] Under nitrogen protection, 27g of diglycidyl terephthalate, 46g of 5-ethyl-5-(p-tolyl)malonyl urea, 27g of triglycidyl isocyanurate, and 4g of benzyltriethylammonium chloride were dissolved in 300g of PGME, and the temperature was raised to 100°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 53.5g of a polymer with Mw=6683Da and PDI=1.59.
[0072] Synthesis example 10
[0073] Under nitrogen protection, 27g of diglycidyl terephthalate, 43g of 5-ethyl-5-(p-tolyl)malonyl urea, 30g of triglycidyl isocyanurate, and 4g of benzyltriethylammonium chloride were dissolved in 300g of PGME, and the temperature was raised to 115°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 60.5g of a polymer with Mw=6751Da and PDI=1.63.
[0074] Synthesis example 11
[0075] Under nitrogen protection, 26 g of diglycidyl terephthalate, 59 g of 5-ethyl-5-(p-tolyl)malonyl urea, 15 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 105°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 58.7 g of a polymer with Mw=6751 Da and PDI=1.66.
[0076] Synthesis example 12
[0077] Under nitrogen protection, 30 g of diglycidyl terephthalate, 50 g of 5-ethyl-5-(p-tolyl)malonyl urea, 20 g of triglycidyl isocyanurate, and 3 g of benzyltriethylammonium chloride were dissolved in 300 g of propylene glycol monomethyl ether (PGME), and the temperature was raised to 120°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 65.7 g of a polymer with Mw=6733 Da and PDI=1.70.
[0078] Synthesis example 13
[0079] Under nitrogen protection, 35 g of diglycidyl terephthalate, 43 g of 5-ethyl-5-(p-tolyl)malonyl urea, 22 g of triglycidyl isocyanurate, and 3 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 110°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 60.5 g of a polymer with Mw=6654 Da and PDI=1.64.
[0080] Synthesis example 14
[0081] Under nitrogen protection, 39 g of diglycidyl terephthalate, 44 g of 5-ethyl-5-(p-tolyl)malonyl urea, 17 g of triglycidyl isocyanurate, and 5 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 120°C. The reaction was kept warm for 10 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 67.2 g of a polymer with Mw=6975 Da and PDI=1.69.
[0082] Synthesis Example 15
[0083] Under nitrogen protection, 24 g of diglycidyl terephthalate, 58 g of 5-ethyl-5-(p-tolyl)malonyl urea, 18 g of triglycidyl isocyanurate, and 5 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 100 ° C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The polymer was filtered and dried to obtain 63.2 g of a polymer with Mw = 6853 Da and PDI = 1.61.
[0084] Comparative Example 1
[0085] The polymer was prepared by the same method as in Synthesis Example 1, except that the amount of monomer a (a in the polymer obtained in this comparative example is 10%) was lower than the range defined in the present invention. The specific process is as follows:
[0086] Under nitrogen protection, 10 g of diglycidyl terephthalate, 50 g of 5-ethyl-5-(p-tolyl)malonyl urea, 40 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of propylene glycol monomethyl ether (PGME), and the temperature was raised to 120°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 53.6 g of a polymer with Mw=5930Da and PDI=1.61.
[0087] Comparative Example 2
[0088] The polymer was prepared by the same method as in Synthesis Example 2, except that the amount of monomer b (75% in the polymer obtained in this comparative example) was higher than the range defined in the present invention. The specific process was as follows:
[0089] Under nitrogen protection, 15 g of diglycidyl terephthalate, 75 g of 5-ethyl-5-(p-tolyl)malonyl urea, 11 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 110°C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 53.2 g of a polymer with Mw=5541 Da and PDI=1.52.
[0090] Comparative Example 3
[0091] The polymer was prepared by the same method as in Synthesis Example 3, except that the amount of monomer c (c in the polymer obtained in this comparative example is 55%) was higher than the range defined in the present invention. The specific process is as follows:
[0092] Under nitrogen protection, 15 g of diglycidyl terephthalate, 30 g of 5-ethyl-5-(p-tolyl)malonyl urea, 55 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 120°C. The reaction was kept warm for 10 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 63.2 g of a polymer with Mw=6035 Da and PDI=1.62.
[0093] Comparative Example 4
[0094] The polymer was prepared by the same method as in Synthesis Example 4, except that monomer a was not added. The specific process is as follows:
[0095] Under nitrogen protection, 60 g of 5-ethyl-5-(p-tolyl)malonyl urea, 40 g of triglycidyl isocyanurate, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 100 ° C. The reaction was kept warm for 12 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The polymer was filtered and dried to obtain 57.9 g of a polymer with Mw = 6315 Da and PDI = 1.60.
[0096] Comparative Example 5
[0097] The polymer was prepared by the same method as in Synthesis Example 5, except that monomer c was not added. The specific process is as follows:
[0098] Under nitrogen protection, 50 g of diglycidyl terephthalate, 50 g of 5-ethyl-5-(p-tolyl)malonyl urea, and 4 g of benzyltriethylammonium chloride were dissolved in 300 g of PGME, and the temperature was raised to 120°C. The reaction was kept warm for 10 hours. After the reaction was completed, the system was cooled to room temperature, and the reaction system was slowly added dropwise to 1000 g of ethanol to precipitate a white solid. The white solid was filtered and dried to obtain 59.3 g of a polymer with Mw=6454 Da and PDI=1.64.
[0099] 2. Preparation of photoresist bottom anti-reflective coating composition:
[0100] Example 1
[0101] 5 g of the polymer obtained in Synthesis Example 1, 2 g of hexamethoxymethylmelamine, and 0.05 g of 1-((3-hydroxyadamantyl)methoxycarbonyl)-difluoromethanesulfonic acid triphenylsulfide were dissolved in 92.95 g of propylene glycol monomethyl ether acetate (PGMEA), and the mixture was filtered through a 0.2 μm filter to obtain a composition 1 for a bottom antireflective coating layer of a photoresist.
[0102] Embodiments 2 to 15
[0103] In the same manner as in Example 1, 5 g of the polymer obtained in Synthesis Examples 2 to 15, 2 g of hexamethoxymethylmelamine, and 0.05 g of 1-((3-hydroxyadamantyl)methoxycarbonyl)-difluoromethanesulfonic acid triphenyl sulfide were dissolved in 92.95 g of propylene glycol monomethyl ether acetate (PGMEA), and the mixture was filtered through a 0.2 μm filter to obtain compositions 2 to 15 for photoresist bottom antireflective coating.
[0104] Comparative Example 1
[0105] 5 g of the polymer obtained in Comparative Example 1, 2 g of hexamethoxymethylmelamine, and 0.05 g of 1-((3-hydroxyadamantyl)methoxycarbonyl)-difluoromethanesulfonic acid triphenyl sulfide were dissolved in 92.95 g of propylene glycol monomethyl ether acetate (PGMEA), and the mixture was filtered through a 0.2 μm filter to obtain Comparative Example Composition 1 for a photoresist bottom anti-reflective coating.
[0106] Comparative Examples 2 to 5
[0107] 5 g of the polymer obtained in Comparative Examples 2 to 5, 2 g of hexamethoxymethyl melamine, and 0.05 g of 1-((3-hydroxyadamantyl)methoxycarbonyl)-difluoromethanesulfonic acid triphenyl sulfide were dissolved in 92.95 g of propylene glycol monomethyl ether acetate (PGMEA), and the mixture was filtered through a 0.2 μm filter to obtain Comparative Example compositions 2 to 5 for photoresist bottom anti-reflective coating.
[0108] 3. Performance test of photoresist bottom coating composition:
[0109] The photoresist bottom anti-reflection coating compositions of the above Examples 1 to 15 and Comparative Examples 1 to 5 were spin-coated onto the etching layer of the silicon wafer, baked at 160° C. for 60 seconds, and then the bottom anti-reflection coating n / k value and film thickness were measured at a wavelength of 193 nm using an ellipsometer, the testing instrument being an ellipsometer (brand / model American Woollam / RC2). The specific test results are shown in Table 1 below.
[0110] Table 1 Performance test results of bottom anti-reflective coating composition
[0111]
[0112] From the data in Table 1 above, it can be seen that the refractive index (n) of the bottom anti-reflective coating (corresponding to composition numbers 1-15) is all greater than 1.8, and the extinction coefficient (k) is all greater than 0.5. A thinner anti-reflective layer can be used, so that the anti-reflective coating can be etched quickly, thereby allowing a shorter etching time, thereby ensuring that the photoresist film is not lost during the etching process. In addition, with the extension of the storage period, the fluctuation value of the corresponding bottom anti-reflective coating refractive index (n) and extinction coefficient (k) is 0.01, which shows that the coating has extremely high stability.
[0113] From the data comparison results of the above comparative bottom anti-reflective coatings (corresponding to comparative composition numbers 1-3), it can be seen that the use of the monomer ratios defined in the present invention can effectively achieve the complementary advantages of each component to obtain a high-quality photoresist bottom anti-reflective coating.
[0114] From the data comparison results of the above comparative bottom anti-reflective coating (corresponding to comparative composition No. 4-5), it can be seen that if the composition contains only two of the three monomers, the coating performance will change significantly. The three monomers can play an excellent synergistic role, effectively improve the refractive index (n) of the bottom coating, and have a large absorbance to light or reflected rays.
[0115] The photoresist bottom anti-reflective coating compositions of the above Examples 1 to 15 and Comparative Examples 1 to 5 were spin-coated onto the etching layer of the silicon wafer, and the bottom anti-reflective coating obtained after baking at 160° C. for 60 seconds was immersed in propylene glycol monomethyl ether, a photolithography solvent, and confirmed to be insoluble. After immersion for 60 seconds, the solvent was dried, and the film thickness was tested again with an ellipsometer (brand / model American Woollam / RC2). The test results are shown in Table 2 below.
[0116] Table 2 Dissolution test of bottom anti-reflective coating
[0117]
[0118] It can be seen from the data in Table 2 above that, by using the ratios of the monomers defined in the present invention, the obtained photoresist bottom anti-reflective coating does not mix with the photoresist layer.
[0119] The bottom anti-reflective coating composition of Example 1 was spin-coated onto the etching layer of the silicon wafer, and baked at 160° C. for 60 seconds to obtain the bottom anti-reflective coating. A 193 nm photoresist based on acrylate was spin-coated on the top of the anti-reflective coating, and exposed at 193 nm. After baking and development, it was observed under a microscope, and it had good lines and no obvious standing wave phenomenon occurred.
[0120] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0121] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A photoresist bottom anti-reflective coating polymer, characterized in that The polymer has the following general formula: ; a, b, and c are respectively the mass fractions of the polymer repeating units; a is selected from 15-55%, b is selected from 20-70%, and c is selected from 10-40%; the weight average molecular weight of the polymer is selected from 1000-10000 Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.0-3.
0.
2. A photoresist bottom anti-reflective coating polymer according to claim 1, characterized in that: a is selected from 25-40%, b is selected from 40-60%, and c is selected from 15-30%.
3. A photoresist bottom anti-reflective coating polymer according to claim 1, characterized in that: The weight average molecular weight of the polymer is selected from 4000-8000 Da, and the molecular weight dispersion coefficient of the polymer is selected from 1.4-2.
3.
4. A method for preparing a photoresist bottom anti-reflective coating polymer according to any one of claims 1 to 3, characterized in that: The preparation method comprises: reacting monomer a, monomer b, monomer c and a catalyst in an electronic grade solvent under an inert gas atmosphere, controlling the reaction temperature and reaction time, and obtaining the polymer through post-treatment after the reaction is completed; The monomer a is diglycidyl terephthalate, the monomer b is 5-ethyl-5-(p-tolyl)malonyl urea, and the monomer c is triglycidyl isocyanurate.
5. The method for preparing a photoresist bottom anti-reflective coating polymer according to claim 4, characterized in that: The catalyst is any one of benzyltriethylammonium chloride, tetrabutylammonium chloride and tetraethylammonium bromide; The electronic grade solvent is any one of propylene glycol methyl ether, 2-hydroxyisobutyric acid methyl ester, propylene glycol monomethyl ether acetate, 3-methoxypropionic acid methyl ester, ethyl lactate, cyclopentanone, dipropylene glycol methyl ether and the like.
6. The method for preparing a photoresist bottom anti-reflective coating polymer according to claim 4, characterized in that: The amount of the catalyst used is 1-10% of the total mass of the monomer a, monomer b, and monomer c; The reaction temperature is 60-150° C., and the reaction time is 8-15 hours.
7. A photoresist bottom anti-reflective coating composition, characterized in that: The photoresist bottom anti-reflective coating composition comprises the polymer according to any one of claims 1 to 3, a cross-linking agent, a photoacid generator and an electronic grade solvent.
8. A photoresist bottom anti-reflective coating composition according to claim 7, characterized in that: The mass fraction of the polymer in the composition is 2-10%, the mass fraction of the crosslinking agent in the composition is 1-3%, the mass fraction of the photoacid generator in the composition is 0.01-0.05%, and the mass fraction of the electronic grade solvent in the composition is 90-95%.
9. A photoresist bottom anti-reflective coating composition according to claim 7, characterized in that: The crosslinking agent is at least one of hexamethoxymethyl melamine, hexabutoxymethyl melamine, tetramethoxymethyl glycoluril, 1,3,4,6-tetrakis (butoxymethyl) glycoluril, tetramethoxymethyl benzoguanamine, and N-hydroxymethyl acrylamide; The photoacid generator is any one or a combination of 1-((3-hydroxyadamantyl)methoxycarbonyl)-difluoromethanesulfonic acid triphenyl sulfide, p-toluenesulfonic acid triphenyl sulfide, trifluoromethanesulfonic acid (p-tert-butoxyphenyl) diphenyl sulfide, 4-tert-butylphenyl diphenyl sulfide nonafluorobutane sulfonate, bis(benzenesulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, trifluoromethanesulfonic acid tri(p-tert-butoxyphenyl) sulfide; The electronic grade solvent is any one of methyl 2-hydroxyisobutyrate, propylene glycol methyl ether, methyl isobutyl carbinol, propylene glycol monomethyl ether acetate, and dipropylene glycol methyl ether.
10. A use of a photoresist bottom anti-reflective coating composition according to any one of claims 7 to 9, characterized in that: The composition is applied to ArF photoresist bottom anti-reflective coating.
Citation Information
Patent Citations
Organic bottom antireflective coating composition for nanolithography
CN105505146A
Bottom anti-reflection film resin, composition and pattern forming method
CN113402703A